2020
DOI: 10.1002/ana.25965
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs Associated With Reversible Cerebral Vasoconstriction Syndrome

Abstract: Objective The purpose of this study was to investigate the significance of circulating micro RNAs (miRNAs) in the pathogenesis of reversible cerebral vasoconstriction syndrome (RCVS). Methods We prospectively recruited 3 independent cohorts of patients with RCVS and age‐matched and sex‐matched controls in a single medical center. Next‐generation small RNA sequencing followed by quantitative polymerase chain reaction (PCR) was used to identify and validate differentially expressed miRNAs, which was cross‐valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…In tuberous sclerosis complex (TSC), high protein expression of MMPs (MMP2, 3, 9, and 14) and TIMPs (endogenous tissue inhibitors 1, 2, 3, and 4) in TSC tubers was associated with BBB dysfunction, while these dysregulated proteins can be partly rescued by miR-146a and miR-147b in tuber-derived TSC cultures [ 204 ]. In reversible cerebral vasoconstriction syndrome (RCVS), high expression of circulating miR-130a-3p was associated with BBB disruption in patients, and overexpression of miR-130a-3p also led to increased BBB permeability in vitro [ 205 ]. Neuropilin-1 (Npn-1) has been suggested to play a critical role in regulating endothelial barrier dysfunction in response to VEGF [ 206 ] or interferon-γ [ 207 ], and Mone et al demonstrated that Npn-1 is a direct target of miR-24, which could negatively regulate Npn-1 mediated endothelial permeability [ 208 ].…”
Section: Non-coding Rnas Regulate Bbb/bscb Functions In Cns Disordersmentioning
confidence: 99%
“…In tuberous sclerosis complex (TSC), high protein expression of MMPs (MMP2, 3, 9, and 14) and TIMPs (endogenous tissue inhibitors 1, 2, 3, and 4) in TSC tubers was associated with BBB dysfunction, while these dysregulated proteins can be partly rescued by miR-146a and miR-147b in tuber-derived TSC cultures [ 204 ]. In reversible cerebral vasoconstriction syndrome (RCVS), high expression of circulating miR-130a-3p was associated with BBB disruption in patients, and overexpression of miR-130a-3p also led to increased BBB permeability in vitro [ 205 ]. Neuropilin-1 (Npn-1) has been suggested to play a critical role in regulating endothelial barrier dysfunction in response to VEGF [ 206 ] or interferon-γ [ 207 ], and Mone et al demonstrated that Npn-1 is a direct target of miR-24, which could negatively regulate Npn-1 mediated endothelial permeability [ 208 ].…”
Section: Non-coding Rnas Regulate Bbb/bscb Functions In Cns Disordersmentioning
confidence: 99%
“…Circulating miRNAs have essential roles in the diagnosis, prognosis, and evaluation of the therapeutic efficacy of different diseases ( 61 , 62 ). During HIV-1 infection, the miRNA profile of the host changes, and miRNA expression varies with disease progression ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…68 One thing of note, an investigation was performed at the molecular level, which found that the abundance of 5miR-NAs (let-7a-5p, let-7b-5p, let-7f-5p, miR-130a-3p, and miR-130b-3p) changed in ictal-stage of migraine by TGF-β signaling pathway and reposed to endothelin-1, indicating that miRNA may play a role in reversible cerebral vasoconstriction syndrome (RCVS) pathogenesis. 69 However, our understanding of the mechanic of headaches is still limited, we need much more further studies through basic clinical trials and animal models.…”
Section: Progresses In the Mechanism Of Headache Disordersmentioning
confidence: 99%